The Role of Managerial Control in The Middle of The Global Crisis Due To Pandemic Covid-19 in Retail Companies - Apiatno Apiatno (SINTESA, 2023)
Since COVID-19 entered Indonesia in February 2020, as a result the Indonesian government is currently taking steps to social distancing activities to the community. Where people are asked to maintain a distance of 1-2 meters when interacting to minimize the spread of the virus. So that schools, universities, offices, agencies under the auspices of the government closed their operational activities and replaced with activities at home. Indirectly, will result in a weakening of the economy so that many retail companies suffer losses and are forced to Terminate Employment. Lack of accurate decision making by a manager will not make retail companies last long. This case study aims to determine the role of Managerial Control in a Manager's decision making. The method used is descriptive and qualitative data forms. This case study states that a manager in an effort to continue the company takes the decision to reduce fixed costs in the form of employee salary costs without looking at the opportunities of the COVID-19 pandemic situation by utilizing technological advances in communication andinformation such as online shops to market their products.